2015
DOI: 10.1515/zna-2015-0251
|View full text |Cite
|
Sign up to set email alerts
|

Fano Antiresonance and Kondo Resonance for Electronic Transport Through a Laterally Coupled Carbon-Nanotube Quantum-Dot System

Abstract: We present nonequilibrium Green function calculations for electronic transport through a laterally coupled carbon-nanotube quantum-dot system. In this system, a one-dimensional double carbon nanotube quantum dot attached to polarised electrodes forms a main channel for electronic tunnelling. Each carbon nanotube quantum dot in the main channel couples to a dangling carbon nanotube quantum dot. Then, the conductance spectrum is calculated. The insulating band and resonance peak in this spectrum, due to Fano ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…48,52 Huo pointed out that one can use the Feynman path analysis to acquire a qualitative understanding of the physical nature of QIs, such as the Kondo resonance and Fano antiresonance, which can be observed in the conductance spectrum of a laterally coupled carbon-nanotube QD system. 53 Since the energy levels of QDs are discrete, electron transport through QDs is thought to occur by resonant tunneling, where the energy of an incident electron coincides with an eigenenergy of the QD. The studies by Gong et al and Huo clearly show that the Feynman path analysis is an effective tool for understanding the propagation of electrons in the resonant tunneling regime.…”
Section: State Of the Art In The Theory Of Qimentioning
confidence: 99%
See 1 more Smart Citation
“…48,52 Huo pointed out that one can use the Feynman path analysis to acquire a qualitative understanding of the physical nature of QIs, such as the Kondo resonance and Fano antiresonance, which can be observed in the conductance spectrum of a laterally coupled carbon-nanotube QD system. 53 Since the energy levels of QDs are discrete, electron transport through QDs is thought to occur by resonant tunneling, where the energy of an incident electron coincides with an eigenenergy of the QD. The studies by Gong et al and Huo clearly show that the Feynman path analysis is an effective tool for understanding the propagation of electrons in the resonant tunneling regime.…”
Section: State Of the Art In The Theory Of Qimentioning
confidence: 99%
“…Datta and co-workers demonstrated that the Feynman path formalism has an intimate relation to a scattering-matrix approach developed to calculate the conductance of disordered systems . Gong et al carried out a Feynman path analysis of electron transport though a parallel double quantum dot (QD) structure, finding that there are infinite electron transmission paths that contribute to a Fano interference. , Huo pointed out that one can use the Feynman path analysis to acquire a qualitative understanding of the physical nature of QIs, such as the Kondo resonance and Fano antiresonance, which can be observed in the conductance spectrum of a laterally coupled carbon-nanotube QD system . Because the energy levels of QDs are discrete, electron transport through QDs is thought to occur by resonant tunneling where the energy of an incident electron coincides with an eigenenergy of the QD.…”
Section: State Of the Art In The Theory Of Qimentioning
confidence: 99%
“…Experiments on quantum dots are generally well described by models where an impurity couples two baths that are not otherwise connected. However, there are also cases where impurities are embedded in a nonequilibrium environment and multiple transport channels are present. Perhaps the simplest examples are side-coupled quantum dots and magnetic break junctions. More complex examples include scanning tunneling microscopy of magnetic atoms, small molecules, and more recently graphene-like nanostructures and molecular chains. , Finally, junctions comprising strongly correlated nanostructures can be approximately mapped onto embedded impurity models. In all these cases, a controlled theoretical treatment is challenging because numerical methods able to reliably access the correlated regime of nonequilibrium quantum impurity models are typically either limited in the level of detail in their description of the baths, especially out of equilibrium, or limited in accuracy by the need to go to high perturbation order (see the Supporting Information). As a result, theoretical work focuses on aspects of the weakly correlated regime or is confined to single- or few-channel correlated transport. …”
Section: The Systemmentioning
confidence: 99%
“…The attached objects act as scatterers for electron transmission through the quantum wire and allow one to tune its transport properties. In T-shaped systems, the interference of different conduction paths can lead to Fano antiresonance manifesting as a dip in the linear conductance [ 23 24 27 28 ]. There are also reports on T-shaped carbon nanotube structures [ 29 30 ] and similar carbon devices engineered by attaching C 60 buckyballs onto the sidewall of a single-walled carbon nanotube (carbon nanobud [ 31 ]).…”
Section: Introductionmentioning
confidence: 99%